Предмет: Алгебра, автор: Аноним

Можете помочь?
Желательно с объяснениями.
Спасибо.
 left { {{ x^{2} -2xy-3 y^{2}=0 } atop { x^{2} -xy-2x-3y=6}} right.

Ответы

Автор ответа: m11m
0
x²-2xy-3y²=0
x²-2xy+y²-4y²=0
(x-y)² - (2y)² =0
(x-y-2y)(x-y+2y)=0
(x-3y)(x+y)=0
x-3y=0                x+y=0
x=3y                   x= -y

При x=3y:
(3y)²-3y*y-2*3y-3y=6
9y²-3y²-6y-3y=6
6y²-9y-6=0
2y²-3y-2=0
D=3²-4*2*(-2)=9+16=25
y₁=(3-5)/4=-0.5         x₁=3*(-0.5)=-1.5
y₂=(3+5)/4=2            x₂=3*2=6

При x=-y:
(-y)² - (-y)*y - 2*(-y) -3y=6
y²+y²+2y-3y-6=0
2y²-y-6=0
D=1-4*2*(-6)=1+48=49
y₁=(1-7)/4=-1.5               x₁=-(-1.5)=1.5
y₂=(1+7)/4=2                  x₂=-2

Ответ: (-2; 2);  (-1.5; -0.5);  (1.5; -1.5);  (6; 2).
Похожие вопросы
Предмет: Немецкий язык, автор: annadarbinyan1